Fiber Saturation Point of Several Indonesian Lesser Known Species - Imam Wahyudi; Arif R. Harijadi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
Fiber saturation point (FSP) of several Indonesian commercial wood species was studied comprehensively. Five wood species namely sengon (Paraserianthes falcataria), gmelina (Gmelina arborea), nangka (Arthocarpus heterophyllus), manii (Maesopsis eminii), and mangium (Acacia mangium) from plantation areas closed to Bogor Agricultural University (IPB) campus were used as the sample. From each species, one normal tree was selected then cut, and one hundred and twenty small healthy blocks of (1 x 1 x 0.5) cm3were extracted randomly and utilized for specific gravity (SG) and wood shrinkage -green to air dry and to oven dry conditions- measurement. FSP was then measured as a ratio of total volumetric shrinkage and the SG. It was showed that FSP was affected by species namely extractive content. In all species studied, average value of FSP was below 30%. FSP of sengon, gmelina, nangka, manii, and mangium in average was 26.41%, 16.92%, 14.49%, 22.31%, and 23.94%, respectively.